Characterization of the Olfactory Receptors Expressed in Human Spermatozoa - Flegel, Caroline; Vogel, Felix; Hofreuter, Adrian; Schreiner, Benjamin S. P.; Osthold, Sandra; Veitinger, Sophie; Becker, Christian; Brockmeyer, Norbert H.; Muschol, Michael; Wennemuth, Gunther; Altmüller, Janine; Hatt, Hanns; et al. (Frontiers in Molecular Biosciences, 2016)
The detection of external cues is fundamental for human spermatozoa to locate the oocyte in the female reproductive tract. This task requires a specific chemoreceptor repertoire that is expressed on the surface of human spermatozoa, which is not fully identified to date. Olfactory receptors (ORs) are candidate molecules and have been attributed to be involved in sperm chemotaxis and chemokinesis, indicating an important role in mammalian spermatozoa. An increasing importance has been suggested for spermatozoal RNA, which led us to investigate the expression of all 387 OR genes. This study provides the first comprehensive analysis of OR transcripts in human spermatozoa of several individuals by RNA-Seq. We detected 91 different transcripts in the spermatozoa samples that could be aligned to annotated OR genes. Using stranded mRNA-Seq, we detected a class of these putative OR transcripts in an antisense orientation, indicating a different function, rather than coding for a functional OR protein. Nevertheless, we were able to detect OR proteins in various compartments of human spermatozoa, indicating distinct functions in human sperm. A panel of various OR ligands induced Ca2+ signals in human spermatozoa, which could be inhibited by mibefradil. This study indicated that a variety of ORs are expressed at the mRNA and protein level in human spermatozoa and demonstrates that ORs are involved in the physiological processes.